2020
DOI: 10.5005/jp-journals-10024-2785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Short-fiber-reinforced Resin Composite Restorations vs Resin Composite Onlay Restorations in Complex Cavities of Molars (Randomized Clinical Trial)

Abstract: Background: Short-fiber-reinforced resin composite (SFRC) is a direct bulk fill resin composite specially indicated in large complex cavities. It is characterized by having high fracture toughness and load bearing capacity to decrease the incidence of fracture of the restoration. Materials and methods: In two parallel groups (n = 38 restorations), 76 participants having complex proximal cavities with asymptomatic vital pulp were randomly enrolled in this trial and received either SFRC (Ever X Posterior, GC, Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…While regarding the results of color match, there was a statistically significant difference between the two groups favoring the microhybrid resin composite restorations. These results in agree with ElAziz et al 2020 7 who reported that a grey color mismatch of SFRC restorations in teeth with dark sclerotic dentin present at the base of the cavity was due to the SFRC is highly translucent material, so the 1-2 mm remaining thickness of the covering microhybrid resin composite layer could not conceal the discolored dentin. Regarding the results of our study in cases of remaining deep stain at the base of the cavity, it is recommended touse an underlying opaquer under SFRC or increase the thickness of overlaying microhybrid resin composite more than 2 mm unlike the manufacturer recommendation that SFRC should be covered by 1-2 m. In contrast to our findings, Guney & Yazici 2020 12 who found that only one SFRC restoration at baseline and 6 months follow up, and two SFRC restorations at 12, 18, and 24 months follow up periods received a score of bravo.…”
Section: Discussionsupporting
confidence: 91%
“…While regarding the results of color match, there was a statistically significant difference between the two groups favoring the microhybrid resin composite restorations. These results in agree with ElAziz et al 2020 7 who reported that a grey color mismatch of SFRC restorations in teeth with dark sclerotic dentin present at the base of the cavity was due to the SFRC is highly translucent material, so the 1-2 mm remaining thickness of the covering microhybrid resin composite layer could not conceal the discolored dentin. Regarding the results of our study in cases of remaining deep stain at the base of the cavity, it is recommended touse an underlying opaquer under SFRC or increase the thickness of overlaying microhybrid resin composite more than 2 mm unlike the manufacturer recommendation that SFRC should be covered by 1-2 m. In contrast to our findings, Guney & Yazici 2020 12 who found that only one SFRC restoration at baseline and 6 months follow up, and two SFRC restorations at 12, 18, and 24 months follow up periods received a score of bravo.…”
Section: Discussionsupporting
confidence: 91%
“…Only minor changes for marginal adaptation, marginal discoloration, color match, and surface texture were observed, and no differences were detected between the evaluated criteria when comparing the baseline with any of the evaluation periods (p<0.05) [23]. Another study showed that no statistically significant difference was observed between fiber-reinforced resin composite and nanohybrid composite restorations tested groups for all USPHS criteria at different follow-up periods except for marginal integrity favoring the fiber restoration at 12 months when the difference became significant (p<0.001), and color match favoring the nanohybrid indirect resin composite restorations with substantial difference in scores at all follow-up intervals (p<0.001) was found [38]. In contrast to our study, everX Posterior and Gaenial Posterior restorations exhibited significant marginal discolorations after three years, and these changes were clinically acceptable and significantly increased over time [37].…”
Section: Discussionmentioning
confidence: 95%
“…The success of the fiber assembly can also be attributed to the discontinuous phase formed by the continuous polymer resin matrix due to the individual mixing of the strip fiber with the nanohybrid composite during restoration. There is also a high chance of void formation in this complex, which is known to form huge areas where oxygen is blocked and, therefore, is known to reduce the bending strength of the fibers [38,40]. Therefore, extreme care must be exercised during placement [41].…”
Section: Discussionmentioning
confidence: 99%
“…Uma das vantagens da realização da restauração por meio de técnica semi-direta com moldagem (extraoral) é a facilidade de adaptação da margem subgengival, por permitir acesso direto e visualização direta da restauração nas margens do preparo no modelo 27 .Outra vantagem da técnica semi-direta é que o profissional pode fornecer ao paciente uma restauração com baixo custo comparada às confeccionadas em laboratório e com possibilidade de confecção em uma única consulta, sem necessidade de restauração provisória (Elaziz et al, 2020;Alharbi et al, 2014).…”
Section: Técnica Semi-diretaunclassified